Role Of Vaman Karma And Shaman Chikitsa In The Management Of Seborrheic Dermatitis- A Case Study - Poonia, Ritesh; Gupta, Arun (International Research Journal of Ayurveda & Yoga, 2020)
Seborrheic Dermatitis is a common skin disease manifests as itchy rash with flaky scales and light patches on darker skin and redness on light skin. The exact cause is still unknown. It is also known as Seborrheic Eczema. In Ayurveda, Seborrheic Dermatitis shares the resemblance with vicharchika, for which Vaman Karma is the choice of treatment. Background: A male patient of 32 years, presents with complaint of scaly patches, red skin, stubborn dandruff, scaling on face and around the nose, along with eyebrows, eyelids, behind the ears with Itching and burning sensation. Intervention and outcome: For the present case Vaman Karma with Madanphala Yoga and Shaman Chikitsa with Mahatikta Ghrit and Aarogyavardhini Vati was given. Results: After complete treatment and 6 months of follow up there was controlling of dermatitis and an improved quality of life.